Mechanical and flammability properties of hybrid recycled newspaper/sepiolite polypropylene composites - Musliha Mohamed, 1988-; Zurina Mohamad, supervisor; Azman Hassan, supervisor; Fakulti Kejuruteraan Kimia (2013)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2013